Distribución y abundancia anual de Ceratium dens (Peridinalcs: Ceratiaceae) en el golfo de California, México - Cortés Altamirano, Roberto; Nuñez Pasten, Arturo (Revista de Biología Tropical, 2000)
Ceratium dens distribution in the Gulf of California was studied based on three oceanographic campaigns, month1y abundance (1995-96) and during three red tide events in Mazatlán Bay. 52 phytoplankton sampIes with a Bongo nel and 64 cm mesh light, during the year 120 water samples with a van Dorn bottIe were collected in two sampling stations and from three red tíde events. Al! samples were counted by the invertedmicroscope method. The results showed that C. dens was present in the upper Gulf of California and sUlToundings of Cabo San Lucas. Two peaks were observed during spring and autumn in MazatIán Bay during 1995- 1996. The highest densities (20-360 cells.·I'I) were observed in coastal areas, whereas ¡he lowest densities (1-14 cells.·I·I) were recorded in the open sea. During red tide events in 1985, 1989 and 1997, 144000-256 000 cells.·I· 1, 100 000-400000 celIs.·I,I, and 189 000-592 000 cells.íil-1 was observed, respectively. During the red tide events C. dens varied, although sometimes was replaced by Skelelonema costatum or Pseudonilzchia spp and Ceratium ¡urca. C. dens, seems to prefer areas with high productivity.